1996
DOI: 10.1002/ijch.199600051
|View full text |Cite
|
Sign up to set email alerts
|

Alignment Photoregulation of a Nematic Liquid Crystal by Surface Adsorption of Aminoalkylated Azobenzenes

Abstract: Adsorption behavior of azobenzenes having an aminoalkyl residue onto a silica surface is described. Immersion of a silica plate in a benzene solution of an aminoalkylated azobenzene resulted in efficient adsorption to form face‐to‐face aggregates which are converted into monomeric states by partial desorption. Silica plates adsorbing the azobenzene bearing an aminoalkyl residue were employed to achieve the surface‐assisted photoregulation of alignment of a nematic liquid crystal between homeotropic and planar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Another method to make polymer surfaces photoactive for LC alignment control involves the surface adsorption of low-molecular-weight azobenzenes. 120 Aminoalkylated azobenzenes are conveniently used for adsorption on surfaces of a fused silica plate and a thin film of poly(acrylic acid) spin cast on a substrate plate. 120 Analogous to surface modification of silica substrates, a thin film of poly(vinyl alcohol) (PVA) was subjected to surface-selective esterification with phexylazobenzene acid chlorides or acetalization with p-hexylazobenzene aldehydes in benzene.…”
Section: Photochromic Polymer Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another method to make polymer surfaces photoactive for LC alignment control involves the surface adsorption of low-molecular-weight azobenzenes. 120 Aminoalkylated azobenzenes are conveniently used for adsorption on surfaces of a fused silica plate and a thin film of poly(acrylic acid) spin cast on a substrate plate. 120 Analogous to surface modification of silica substrates, a thin film of poly(vinyl alcohol) (PVA) was subjected to surface-selective esterification with phexylazobenzene acid chlorides or acetalization with p-hexylazobenzene aldehydes in benzene.…”
Section: Photochromic Polymer Surfacesmentioning
confidence: 99%
“…The polymer is adsorbed spontaneously to make the silica surface photoactive. Another method to make polymer surfaces photoactive for LC alignment control involves the surface adsorption of low-molecular-weight azobenzenes . Aminoalkylated azobenzenes are conveniently used for adsorption on surfaces of a fused silica plate and a thin film of poly(acrylic acid) spin cast on a substrate plate …”
Section: Photochromic Polymer Surfacesmentioning
confidence: 99%
“…If an azobenzene-containing polymer thin film is in contact with another matrix, for example, a layer of liquid crystals (LCs), the photoisomerization reaction of azobenzene moieties may induce reversible switching of the liquid crystal (LC) alignment between two different aligned states, subject to the formation of preoriented LC monodomains . Generally, the preorientation of LCs could be realized via different approaches, including applying electric/magnetic fields, polarized laser irradiation, or shear flow; doping dyes into LC assemblies; ,, fabricating azobenzene−polymer networks , or by self-assembly of monolayers; , use of fluoropolymer surfaces, rubbed polymer surfaces, patterned surfaces, surface relief gratings, , and surfaces with selective adsorption, , to name but a few. A simple yet efficient approach that integrates the alignment function with a satisfactory photoswitching performance is to utilize the Langmuir−Blodgett−Kuhn (LBK) technique for fabricating thin layers with supramolecular architectures from azobenzene-containing polymeric amphiphiles.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical structures of materials used in this study are shown in Fig.2. Poly(acrylic acid) (pAA, M w ~2.5610 5 ) was purchased from Aldrich.4-(10-Aminodecyloxy)-4'-butylazobenzene (4AzA) was prepared according to our previous paper 23. Octadecylamine (C18A) was obtained from Kanto Chemical Co. and used after puri®cation by recrystallization from hexane.…”
mentioning
confidence: 99%